Progressive Neurochemical Abnormalities in Cognitive and Motor Subgroups of Amyotrophic Lateral Sclerosis: A Prospective Multicenter Study. (24th August 2021) - Ta, Daniel; Ishaque, Abdullah; Srivastava, Ojas; Hanstock, Chris; Seres, Peter; Eurich, Dean T.; Luk, Collin; Briemberg, Hannah; Frayne, Richard; Genge, Angela L.; Graham, Simon J.; Korngut, Lawrence; et al.
Abstract : Objective: To evaluate progressive cerebral degeneration in amyotrophic lateral sclerosis (ALS) by assessing alterations in N -acetylaspartate (NAA) ratios in the motor and prefrontal cortex within clinical subgroups of ALS. Methods: Seventy-six patients with ALS and 59 healthy controls were enrolled in a prospective, longitudinal, multicenter study in the Canadian ALS Neuroimaging Consortium. Participants underwent serial clinical evaluations and magnetic resonance spectroscopy at baseline and 4 and 8 months using a harmonized protocol across 5 centers. NAA ratios were quantified in the motor cortex and prefrontal cortex. Patients were stratified into subgroups based on disease progression rate, upper motor neuron (UMN) signs, and cognitive status. Linear mixed models were used for baseline and longitudinal comparisons of NAA metabolite ratios. Results: Patients with ALS had reduced NAA ratios in the motor cortex at baseline ( p < 0.001). Ratios were lower in those with more rapid disease progression and greater UMN signs ( p < 0.05). A longitudinal decline in NAA ratios was observed in the motor cortex in the rapidly progressing ( p < 0.01) and high UMN burden ( p < 0.01) cohorts. The severity of UMN signs did not change significantly over time. NAA ratios were reduced in the prefrontal cortex only in cognitively impaired patients ( p < 0.05 ) ; prefrontal cortex metabolites did not change over time. Conclusions: Progressive degeneration of the motor cortex in ALS is associated with more aggressive clinical presentations. These findings provide biological evidence of variable spatial and temporal cerebral degeneration linked to the disease heterogeneity of ALS. The use of standardized imaging protocols may have a role in clinical trials for patient selection or subgrouping. Classification of Evidence: This study provides Class II evidence that MRS NAA metabolite ratios of the motor cortex are associated with more rapid disease progression and greater UMN signs in patients with ALS. Trial Registration Information: ClinicalTrials.gov Identifier: NCT02405182.